Diagnosis and Improvement in a Fresh Grape Agro- Exporting Company Using Management Techniques - Tejada Guevara, Sherghei Aaron (2025)
This article focuses on the optimization of production areas in an agro-export grape company through the application of various management techniques and practical improvements. For this, a mixed methodology was used, which includes the analysis of quantitative and qualitative data, such as process flowcharts, diagrams, and records. Among the improvements implemented, the redesign of the conveyor belt was included, which reduced ergonomic injuries and work absences, with average adjustments between 92.82 and 105.6 cm. In addition, the 5S methodology was implemented, which increased management by 89.1%. Concrete changes were made, such as the automation of pallet labelling and the relocation of staff, which allowed increasing productivity and recovering the investment in 5.2 months. As a result, productivity improved by 18.57% in women and 23.86% in men, and efficiency increased by 95.9%.